2003
DOI: 10.4049/jimmunol.170.3.1579
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tissue Depresses While Tumor Tissue Enhances Human T Cell Responses In Vivo to a Novel Self/Tumor Melanoma Antigen, OA1

Abstract: Antitumor T cells often recognize targets that are nonmutated “self” tissue differentiation Ags, but the relative impact of Ag expression by normal and transformed tissue for a human self/tumor Ag has not been studied. To examine the influence of self-tolerance mechanisms on the function of self/tumor-specific T cell responses in humans, we sought to identify an Ag that was expressed, processed, and presented in an MHC-restricted fashion by tumor cells, but for which there was the human equivalent of a “knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…Immunity to cancer-testis antigens is generally not present in healthy individuals, and becomes detectable in patients with cancer, but is associated with a poor prognosis ( 38, 39 ). Immunity to tissue-associated differentiation antigens, particularly those defined as targets for melanoma-specific T-cells, is also elevated in melanoma patients ( 40, 41 ), but is believed to be compromised by self-tolerance ( 42, 43 ). Importantly, none of the healthy donors in which these memory-compartment associated immune responses were evident showed any signs of autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Immunity to cancer-testis antigens is generally not present in healthy individuals, and becomes detectable in patients with cancer, but is associated with a poor prognosis ( 38, 39 ). Immunity to tissue-associated differentiation antigens, particularly those defined as targets for melanoma-specific T-cells, is also elevated in melanoma patients ( 40, 41 ), but is believed to be compromised by self-tolerance ( 42, 43 ). Importantly, none of the healthy donors in which these memory-compartment associated immune responses were evident showed any signs of autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…The immunologic effects of self-antigen expression on MHC class I and II-restricted T cell frequency, avidity and function have been demonstrated in murine models involving germline antigen loss to the MDA's gp100 and Tyrosinase (26, 27), and in a human model involving the MDA OA1 (ocular albinism I) (28). Based on the compelling data shown by these antigen knockout studies, we felt that TRP-1 was a highly relevant experimental self-antigen, uniquely suitable for experiments focused on CD4-based tumor immunity, autoimmunity and self-tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…One reason might be the relative non-immunogenicity of most TAA, although immunogenicity is not exclusively an intrinsic feature of an antigen as it also depends on the level of TAA exposure to the immune system of an organism [190]. To address this issue, investigators have reported that immunization with a xenogeneic homologue of TAA or an allogeneic cell vaccine genetically modified to express alpha(1,3)galactosyltrasferase (a xenotransplantation antigen) overcame immune tolerance to weakly immunogenic self antigens and controlled tumor growth in animals [191][192][193][194].…”
Section: Inflammation and The Immunological Sense Of Dangermentioning
confidence: 99%